Role of Hospital Management in Health Related Issues: The Impact of Hospital Management on Health and National Development (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The nation’s prosperity and happiness lies in the health of its citizens. Good health is a fundamental human right, and each country is responsible for the provision of adequate health facilities for its population, since health and development are closely inter-twined and inseparable aspects of the government. Promotion of health is essential for national progress.Health contributes to a better quality of life and World peace. The health of a nation is not only an essential component to the nation’s economic growth but also for internal stability. Assuring a minimal level of health care to the population is a critical constituent of the development process. Hospitals and health centers play a vital role in protection of health of the people. Good health delivery is always associated with better capability and leadership.